An on-chip microfluidic pressure regulator that facilitates reproducible loading of cells and hydrogels into microphysiological system platforms - Wang, Xiaolin (Lab Chip, 2016)
Coculturing multiple cell types together in 3-dimensional (3D) cultures better mimics the in vivo microphysiological environment, and has become widely adopted in recent years with the development of organ-on-chip systems. However, a bottleneck in set-up of these devices arises as a result of the delivery of the gel into the microfluidic chip being sensitive to pressure fluctuations, making gel confinement at a specific region challenging, especially when manual operation is performed. In this paper, we present a novel design of an on-chip regulator module with pressure-releasing safety microvalves that can facilitate stable gel delivery into designated microchannel regions while maintaining well-controlled, non-bursting gel interfaces. This pressure regulator design can be integrated into different microfluidic chip designs and is compatible with a wide variety of gel injection apparatuses operated automatically or manually at different flow rates. The sensitivity and working range of this pressure regulator can be adjusted by changing the width of its pressure releasing safety microvalve design. The effectiveness of the design is validated by its incorporation into a microfluidic platform we have developed for generating 3D vascularized micro-organs (VMOs). Reproducible gel loading is demonstrated for both an automatic syringe pump and a manually-operated micropipettor. This design allows for rapid and reproducible loading of hydrogels into microfluidic devices without the risk of bursting gel-air interfaces.